Super giant basal cell carcinoma in an autistic patient: A case report - Hudson, Emma (SAGE Open Med Case Rep, 2020)
Basal cell carcinoma is the most common skin cancer in the world and is generally treated when small in size with an excellent prognosis. Rarely, basal cell carcinoma will grow to be larger than 5 cm, at which point they are termed giant basal cell carcinoma. Giant basal cell carcinoma comprises only 0.5% of all basal cell carcinoma, but is associated with impaired quality of life and increased risk of metastasis. When a basal cell carcinoma grows to over 20 cm in size, it is termed super giant basal cell carcinoma. Here, we report a case of both a super-giant basal cell carcinoma and a giant basal cell carcinoma developing over 10–12 years on the upper back and anterior chest wall of an autistic male. Generally, this presentation is associated with neglect on the part of the patient. This case report demonstrates a super-giant basal cell carcinoma developing secondary to patient neglect in the context of comorbid mental illness.